Tailoring lanthanide nanocrystals for nanomedicine - Zhang, Yan (2013)
Lanthanide nanocrystals have demonstrated strong potentials in nanomedicine due to its up-conversion and strong magnetic properties, and low toxicity. This talk will focus on strategies in lanthanide nanostructure tailoring to achieve up-conversion color emission tuning, MRI T1 and T2 contrast tuning, and the use of up-conversion fluorescence in drug delivery and cancer cells ablation.